The therapeutic potential of exercise in post-traumatic stress disorder and its underlying mechanisms: A living systematic review of human and non-human studies [version 3; peer review: 1 approved, 2 approved with reservations] - David Gilbert; Thomy Tonia; Edoardo G. Ostinelli; Toshi A. Furukawa; Hossein Dehdarirad; Emily Sena; Fiona Ramage; Spyridon Siafis; Virginia Chiocchia; Claire Stansfield; Simonne Wright; Francesca Tinsdeall; et al. (Wellcome Open Research)
Background Exercise for post-traumatic stress disorder (PTSD) is a potentially effective adjunct to psychotherapy. However, the biopsychosocial mechanisms of exercise are not well understood. This co-produced living systematic review synthesizes evidence from human and non-human studies. Methods We Included controlled human and non-human studies involving searches of multiple electronic databases (until 31.10.23). Records were screened, extracted, assessed for risk of bias, and reconciled by two independent reviewers. The primary outcome for human studies was PTSD symptom severity, while outcomes of interest for non-human studies included freezing behaviour, fear memory, fear generalization, startle response, and locomotion. Data were synthesised with random-effects meta-analysis. Results Eleven human studies met the eligibility criteria. Overall, exercise was not associated with symptom severity improvement compared to control (standardized mean difference [SMD] -0.08, 95% confidence interval [CI] -0.24 to 0.07; 8 studies, one at low risk of bias). High-intensity exercise reduced PTSD symptoms scores more than moderate-intensity exercise. There was insufficient data to examine the effects of exercise on functional impairment, PTSD symptom clusters, and PTSD remission. Only three studies, all at high risk of bias, examined mechanisms of exercise with inconclusive results. Exercise was associated with improvement in all behavioural outcomes, including locomotor activity (SMD 1.30, 95% CI 0.74 to 1.87, 14 studies), and changes in several neurobiological markers, including increase in brain-derived neurotrophic factor (SMD 1.79, 95% CI 0.56 to 3.01). Conclusions While non-human studies provide compelling evidence for the beneficial effects of exercise, human trials do not. Evidence from non-human studies suggest that exercise might increase the levels of brain-derived neurotrophic factor, enhance cognitive appraisal, and improve perceived exertion. Overall, the paucity of data on the effectiveness of exercise in PTSD and mechanisms of action underscore the need for rigorous trials. Registration The protocol was registered with PROSPERO (ID:453615; 22.08.2023).